INCREASING THE LEVEL OF ENERGY CONSUMPTION EFFICIENCY IN KINDERGARTEN AND ITS IMPACT ON THE LEVEL OF THERMAL COMFORT - ДЕШКО, В. І.; БІЛОУС, І. Ю.; БУЯК, Н. А.; САПУНОВ, А. О. (Technologies and Engineering, 2023)
Introduction. People spend about 90% of their time indoors, so a comfortable indoor thermal environment is essential for high levels of productivity and well-being. Assessment of indoor thermal comfort is a key point in the design and operation of heating and ventilation systems, as well as in improving the energy efficiency of buildings. Purpose. To improve the energy efficiency of buildings and assess the change in thermal comfort for highly sensitive groups of the population on the example of kindergarten visitors with improved thermal protection. Methodology. The research is carried out using computer modeling in the DesiqnBuilder software. Findings. Using computer modeling, we determined the energy demand, additional heat gain and heat loss of a building with different levels of thermal protection and different modes of heating and ventilation. The impact of increasing the level of energy efficiency on thermal comfort was investigated. Originality. To study the impact of increasing the level of energy efficiency of a building on the level of thermal comfort using computer modeling. Practical value. Using computer modeling, a 3D model was built and the energy consumption of the building was determined before and after increasing the level of energy efficiency, as well as the impact of building modernization on the level of thermal comfort.